Surface modification of activated carbon from sago waste - TOGIBASA, Octolia; DAHLAN, Khaeriah; ANSANAY, Yane Oktovina; RUNGGAWERI, Alda Filadelfi; MERANI, Marlifon (Journal of Metals, Materials and Minerals, 2023)
In this paper, we analyzed the effect of surface modification on the surface properties of the active carbon from sago waste using varied oxidizers, namely H2O2, HNO3, and H2SO4. The ordinary active carbon has an initial surface area of ​​546.6 m2∙g-1, with a phenol and carboxylic functional group. The porosity, functional groups and morphological surface, together with the chemical composition of activated carbon were examined using a nitrogen adsorption-desorption through the Brunauer Emmett Teller (BET) method and the calculation of Barret-Joyner-Hall (BJH), a Fourier-transformed infrared spectroscopy, and a scanning electron microscopy with energy dispersive spectroscopy. The results found that the modified activated carbon significantly increased surface area and total pore volume. Activated carbon modified using H2SO4 oxidizers has the highest surface area value of 853.6 m2∙g-1 and a total pore volume value of 0.585 cm3∙g-1. In addition, the surface modification has changed carbon's porosity from micropore to mesopore, altered the surface functional group from phenol to ether. The surface modification has improved its adsorption capacity and potentially further its application. In conclusion, modifying the surface could make the properties closer to the standards for commercial activated carbon.